The Method of Aesthetic Transfer as a Didacticprinciple in Museum Pedagogy - Kozjek Varl, Katja; Duh, Matjaž; Herzog, Jerneja (Revija za elementarno izobraževanje, 2022)
Previous research has shown that the method of aesthetic transfer works successfully in preschool as well as in primary and secondary education when it comes to regular forms of teaching. In this study, we were interested in how this principle can be implemented in museum education in an authentic gallery space. To this end, a case study was conducted with a sample of 55 students aged 12-14 (n = 55). The method of aesthetic transfer was tested on 4 works in the Maribor Art Gallery. The results show that the method of aesthetic transfer proved to be a successful didactic principle even in the gallery space, especially as a successful principle for learning about contemporary visual art.
Keywords: Method of aesthetic transfer, art appreciation, museum pedagogy, gallery, elementary school